Vividness of Object and Spatial Imagery. Issue 2 (April 2016) - Blazhenkova, Olesya
Vividness is one of the fundamental characteristics of visual mental imagery. The first research goal was to examine whether vividness that refer to imagery of pictorial object (color, texture, or shape) versus spatial (three dimensional structure, location, or mechanism) properties constitute separate vividness dimensions. The second goal was to develop a vividness questionnaire separately assessing dimensions of imagery vividness. In Study 1, 111 students ( M age = 21.8 years, SD = 1.3) evaluated the vividness of imagery evoked by nine object and nine spatial items from the pilot version of the new Vividness of Object and Spatial Imagery (VOSI) questionnaire, completed a self-report assessment of object and spatial imagery, and rated their aptitudes in art and science. Analysis indicated that imagery vividness comprised object and spatial dimensions. Object vividness items were positively associated with the self-report measure and ratings of artistic abilities, whereas spatial vividness items were positively associated with self-report measure and ratings of science abilities. In Study 2, an independent sample of 205 students ( M age = 21 years, SD = 1.7) completed the second version of the VOSI, art and science aptitude ratings, and a number of self-report and performance measures assessing object and spatial imagery. Object and spatial imagery vividness items loaded on factors with 28 retained items; this two-factor vividness model fit the data better than a unidimensional vividness model. The questionnaire had satisfactory Cronbach's α for object vividness scale (.88) and for spatial vividness scale (.85). Correlational analyses supported convergent and discriminative validity of the VOSI. While object imagery vividness and spatial imagery vividness share some underlying vividness variance, they are dissociated into separate dimensions.